A new approach for synchro shaft position measurement using pulse width modulation. (1st January 2014) - Deepak, Ch.; Venkat Kishore, G.; Vadarevu, Rajesh; Amarendra, G.
In this paper, an angle measurement system for a synchro transmitter is presented. It is based on the concept of pulse width modulation, which enables determination of the shaft angle of a synchro transmitter. A dedicated electronic scott-T gives the resolver format signals from a synchro transmitter. Triangular signal is used along with scott-T sine, cosine signals to generate pulse width modulated signals. The linear evaluation of time duration window (TDW), the quadrant detection and shaft angle in digital form demonstrates the effectiveness of the proposed converter. The measurement system is designed using op-amps, complex programmable logic device (CPLD) and a microcontroller. The microcontroller software design is also introduced. The experimentation on designed board with real synchro's outputs has been demonstrated to validate the proposed approach.